TINJAUAN CAFÉ INSTAGRAMABLE PADA ONE EIGHTY COFFEE BANDUNG - Zein, Anastasha Oktavia Sati; Rachim, Aldrian Agusta (ATRAT: Jurnal Seni Rupa, 2018)
There are many ways and efforts to make cafes become the main destination of the audience, including One Eighty Coffee which strives for space design and experience that will be obtained by its customers so that becomes the pride of anyone who can attend and capture it on social media. Each corner of the interior space is designed in such a way that it is unique so that the images will be obtained from an instgramable photo session. An unforgettable experience that deserves to be captured on the customer’s preferred social media, especially on Instagram.Keywords: Instagramable, Design Interactive, Café_______________________________________________________________  Banyak cara dan upaya agar café menjadi tujuan utama para penikmatnya, tidak terkecuali One Eighty Coffee yang mengupayakan desain ruang beserta pengalaman yang akan diperoleh pelanggannya agar cukup instagramable serta menjadi kebanggaan siapa saja yang bisa hadir serta mengabadikannya di media sosial. Setiap sudut ruang interior dirancang sedemikian rupa dengan keunikan sehingga akan diperoleh hasil gambar dari sesi foto yang instgramable. Pengalaman yang tidak akan terlupakan dan layak diabadikan dalam media sosial pilihan pelanggan terutama di instagram.Kata Kunci: Instagramable, Desain Interaktif, Café